2008
DOI: 10.1210/me.2007-0410
|View full text |Cite|
|
Sign up to set email alerts
|

Antidiabetogenic Effects of Chromium Mitigate Hyperinsulinemia-Induced Cellular Insulin Resistance via Correction of Plasma Membrane Cholesterol Imbalance

Abstract: Previously, we found that a loss of plasma membrane (PM) phosphatidylinositol 4,5-bisphosphate (PIP2)-regulated filamentous actin (F-actin) structure contributes to insulin-induced insulin resistance. Interestingly, we also demonstrated that chromium picolinate (CrPic), a dietary supplement thought to improve glycemic status in insulin-resistant individuals, augments insulin-regulated glucose transport in insulin-sensitive 3T3-L1 adipocytes by lowering PM cholesterol. Here, to gain mechanistic understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Therefore, it is likely that increased RhoE GTPase per se may also play an important role in insulin resistance in type 2 diabetes in vivo. In this regard, studies with epitrochlearis muscles demonstrated that cortical F-actin was reduced in insulin-resistant obese Zucker rats compared with insulin-sensitive lean littermates, providing evidence that the abnormality of cytoskeletal reorganization could contribute to this insulin-resistant state (12). Future studies are needed to determine the physiological role of RhoE in the regulation of insulin sensitivity and glucose homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is likely that increased RhoE GTPase per se may also play an important role in insulin resistance in type 2 diabetes in vivo. In this regard, studies with epitrochlearis muscles demonstrated that cortical F-actin was reduced in insulin-resistant obese Zucker rats compared with insulin-sensitive lean littermates, providing evidence that the abnormality of cytoskeletal reorganization could contribute to this insulin-resistant state (12). Future studies are needed to determine the physiological role of RhoE in the regulation of insulin sensitivity and glucose homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, Sreejayan et al (19) reported that Cr treatment decreased liver triglyceride levels and lipid accumulation in animal models. Horvath et al (20) reported that Cr activates Glut-4 trafficking via a cholesterol-dependent mechanism and concluded that Cr 3+ supplementation may lower blood glucose by altering the plasma membrane composition of cholesterol in fat and muscle cells. However, there have been no reports assessing myocellular lipids in human studies evaluating Cr supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…135 One potential alternative is to use drugs that sequester plasma-membrane cholesterol, such as cyclodextrins, 24,136 which reduce intracellular cholesterol and inflammation 137 and increase insulin sensitivity in adipocytes in vitro . 138140 Long-term studies of experimental treatment with hydroxy-propyl-β cyclodextrin (HPBCD) for compassionate use in Niemann–Pick disease are ongoing. 141 We reported a beneficial effect of HPBCD on DKD in the leptin-deficient BTBR ob/ob murine model of T2DM.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%